Determinants of bather hygiene in public swimming pools: a mixed-methods analysis of online discussion comments. (1st June 2022) - Young, Ian; Robillard, Paige; Loeffler, Pauline; Sekercioglu, Fatih
Abstract: Swimming in public pools can expose bathers to microbiological (e.g., Cryptosporidium ) and chemical (e.g., disinfection by-product) hazards, which can lead to recreational water illness. Adequate hygienic behaviours among bathers are important to reduce these risks. However, prior studies have found low compliance with pre-swim showering and avoidance of urinating in pools. We conducted a mixed-methods analysis of online discussion comments to identify key determinants of these two behaviours. We identified relevant discussion threads on Reddit, Quora, and swimming forums. Identified comments were classified as having a positive or negative sentiment towards the behaviour, and they were thematically analyzed according to the Theoretical Domains Framework (TDF). We analyzed 986 comments from 45 threads; 49.8% of comments were classified as expressing a positive sentiment towards the behaviour. Positive sentiments were more commonly expressed towards pre-swim showering compared to avoidance of urinating in pools (60.1 vs. 47.1%). Eleven themes were identified across the following eight TDF domains: beliefs about consequences ( n = 362 comments), social influences ( n = 298), beliefs about capabilities ( n = 240), social/professional role and identity ( n = 144), knowledge ( n = 138), emotions ( n = 137), reinforcement ( n = 78), and environmental context and resources ( n = 33). Results can help to inform targeted educational and outreach strategies with bathers to encourage increased adoption of hygienic behaviours. HIGHLIGHTS: Users in online forums have inconsistent beliefs towards hygienic behaviours in swimming pools. Positive beliefs were more commonly expressed towards pre-swim showering compared to avoiding urinating in pools. Behaviours were mostly influenced by expectations of other swimmers, outcome expectancies, and self-efficacy. Other important factors related to risk perceptions, etiquette, emotions, and misconceptions. Graphical Abstract